Pengetahuan asas politik Malaysia - Mohd. Foad Sakdan (Kuala Lumpur : Dewan Bahasa dan Pustaka, 1997)
Principles of Malaysian politics
Includes index
Bibliography : p. 187-190
In Malay
Keywords: Political parties -- Malaysia; Associtions, institutions, etc. -- Malaysia; Malaysia -- Politics and government